Exploring longitudinal associations between farmer health and well-being and dairy herd subclinical mastitis prevalence and productivity: The HUNT Study, Norway - N.A. Steen; E.M. Rosvold; M.O. Torske (Journal of Dairy Science)
ABSTRACT: The health and well-being of farmers is one aspect of the sustainability of agriculture, as is the health and productivity of livestock. Previous research suggests a possible association between the two, but the complexity of the relationships between farmers and their livestock can hamper research efforts. This observational study uses high quality existing survey and register data from a cohort of Norwegian dairy enterprises to explore possible longitudinal associations between farmer health and well-being (general health, chronic disease or condition, chronic pain, anxiety or depression symptoms, or poor life satisfaction) and changes in dairy herd udder health (estimated by the proportion of milk tests with a high somatic cell count [SCC%]) or milk yield (kg/cow-year Eq). We found evidence of a general trend toward increased SCC% with poor farmer health or well-being. If the farmer had poor self-reported general health, the odds ratio (OR) for a 1-yr increase in SCC% at the enterprise was 1.51 (95% CI: 0.76, 2.99) and 1.80 (0.71, 4.51) after adjustment for possible effect modifiers, compared with those with good health, and for poor life satisfaction the OR was 1.50 (0.71, 3.15) and 2.61 (0.92, 7.39) after adjustment. We also find evidence that enterprises where a farmer was experiencing poor health or well-being tended to have lower odds of a decrease in milk yield than other enterprises. The OR for a 1-yr decrease in milk yield with any chronic disease or condition was 0.42 (0.24, 0.76), and with symptoms of anxiety or depression the OR was 0.56 (0.23, 1.34). Potential confounders and effect modifiers are discussed and explored. These results suggest that further longitudinal research to unravel the relationships between farmer health and well-being, and livestock health and productivity is needed.